KONSTRUKSI MASYARAKAT PENCARI SUMBANGAN DI JALAN RAYA (Studi Kasus Pencarian Amal Masjid Di Jalan Raya Kabupaten Pamekasan) - Holis, Mohammad (STAIN PAMEKASAN, 2017)
The phenomenon of charityâs conducting in highway for the establishing meant of mosque has been levelly occurred, in certain Islamic community. The levelness phenomenon is viewed from the perspective of sociology, however it is important to research the phenomenon by focusing on (1) the characteristics of religiosity of the member of society, the charity collector (2) the rationalization of charity collector behavior (3) the description of social meaning of charity collection in the highway.The research methodology with certain insistences, includes: the use of qualitative approach and emic perspective. The technique of data gathering uses observation, depth interview, ethno methodology and documentation based on the problem of research, on the strategy of research is divided into phases, namely, in the field of research, informationâs gathering and data analysis. The later (data analysis) uses the procedure of induction, conceptualization and interpretation by applying double hermeneutic. Moreover the observation of validity of research uses triangulation member check technique and the lengthen of researcherâs presentation. The research obtain some important information about the social meaning of charityâs conducting for the establishment of mosque in highway, as follows (1) the process of âreligion likeâ for social activity or the covering of social activity in the name or religion (2) the realization of publicâs of publicâs disbelief against committee, manager and organizer of mosque establishment.Such information carry out the implication: (1) religion is the only one culture explaining humanâs way of live, (2) religion is closely fastened to publicâsÂ aspects of live, (3) the deconstruction on Islamic missionary concept or Islam missionary is directed to the domination of Islamâs social which maintains Islamâs social dimension.